AHMAD MARZUQI AL-BĀTĀWĪ’S THOUGHTS IN FAḌL AL-RAḤMĀN BOOK AND ITS IMPLEMENTATION ON DETERMINING ISLAMIC CALENDAR IN INDONESIA - Yaqin, Ahmad Ainul; Rohman, Khabib Syaikhu; Faza, Ricka Ulfatul (Fakultas Syari'ah dan Hukum UIN Walisongo, 2023)
Criteria for the visibility of the new moon have been initiated by Betawi ulama, one of which is found in the book Faḍl al-Raḥmān by Ahmad Marzuqi al-Bātāwī. Ahmad Marzuqi's criteria are very different from those used by the Indonesian Ministry of Religion, giving rise to several differences. Using literature research and interviews as a data collection method, this paper finds that Ahmad Marzuqi al-Bātāwī's thoughts in the book Faḍl al-Raḥmān state that the minimum limit for imkān al-rukyah is 7° without using a telescope. This idea of imkān al-rukyah is still currently being implemented by the al-Marzūqiyyah congregation in Cipinang Muara, East Jakarta, in determining the start of the lunar month so that if the height of the new moon is less than 7° it causes differences with the government.